Hot books in the Cold War : the CIA-funded secret Western book distribution program behind the Iron Curtain - Reisch, Alfred A. (Alfred Alexander), 1931-2013 (Central European University Press, 2013)
This book tells the story of the secret book distribution program financed by the CIA to Eastern Europe during the Cold War. The book program, at its height between 1957 and 1970, was one of the least known but most effective methods of penetrating the Iron Curtain, and reached thousands of intellectuals and professionals in the Soviet Bloc. The author conducted thorough research on the key personalities involved in the book program, especially the two key figures: S.S. Walker, who initiated the idea of a "mailing project," and G.C. Minden, who developed the program into one of the most effective political and psychological tools of the Cold War. The book includes chapters on the vagaries of censorship and on the interception of books by communist authorities based on personal letters and accounts from recipients of Western material.